Comparison of demographic characteristics and haematological parameters in newborns with and without haemolytic disease due to ABO incompatibility - Sahin, Kamil; Aydın, Tahir; Bilgin, Demet Deniz; Büyükkayhan, Derya; Elevli, Murat (BMC pediatrics, 2025)
ABO incompatibility is the most common blood group incompatibility in newborn babies, haemolytic disease develops in very few cases and is much milder than Rh incompatibility. In our study, we aimed to retrospectively examine the changes in platelet parameters, in addition to the expected decrease in the erythrocyte count, in immunized ABO incompatible patients, by comparing them with those in the control group. The demographic data and laboratory results of patients born in our hospital between November 1, 1997, and December 31, 2023, who had accessible information, were examined. The haemogram parameters of newborns with haemolytic disease who did not have ABO incompatibility those of newborns with ABO incompatibility and those of newborns with positive direct anti-globulin test results were compared using statistical methods. A total of 5,198 out of 7,780 newborns were included in the study. A total of 2582 newborns for whom demographic and laboratory values ​​could not be obtained were excluded from the study. When the data of 5,158 newborns without incompatibility and 40 newborns with haemolytic disease due to ABO incompatibility were compared, the mean red blood cell (RBC), haematocrit, haemoglobin and mean platelet volume (MPV) values of newborns with haemolytic disease were found to be statistically significantly lower than those of newborns in the control group, whereas the platelet, mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and red cell distribution width (RDW) values were greater. Thrombocytopenia was not observed in any patient. Haemolytic disease due to ABO incompatibility is a mild haemolytic disease that is thought to be caused by maternal antibody density or low antigen density on neonatal erythrocytes. We detected an increase in the platelet count and a decrease in the erythrocyte count values in in the haemolytic group. Prospective studies are needed on this subject that also examine erythropoietin and thrombopoietin values.